Prescription Pattern of Antibiotics at Outpatients Department of Gynaecology and Obstetrics in a Teaching Hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2023)
Background: Antibiotics are usually prescribed based on the clinical features of infections. Objective: The purpose of the present study was to assess the prescription pattern of antibiotics at outpatients Department of Gynaecology and Obstetrics in a teaching hospital in Bangladesh. Methodology: This cross-sectional study was carried out among patients attending the outpatients’ department (OPD) of Obstetrics and Gynaecology from October 2014 to April 2015 in Rajshahi Medical College and Hospital, Rajshahi, Bangladesh. The demographic details, average number of drugs per prescriptions, percentage of drugs prescribed by generic names, percentage of encounters with an antibiotic and an injection prescribed, percentage of drugs prescribed from Essential Drug List (EDL) of Bangladesh, percentage of encounters with prescription of antiulcerant, NSAID, multivitamin and multimineral, iron preparation and a calcium preparation were noted. Results: A total number of 384 women were recruited for this study. The age group of 20 to 29 years accounted for the highest number 180 (46.8%) and from the age group of 70 to 79 years accounted for the lowest number 2 (0.5%) patients. Groups of drug which commonly prescribed were anti-ulcerant 247. The other commonly prescribed group of drugs were iron preparations 235, calcium preparations 182, antimicrobials 160, multivitamins and multi-minerals 147, antispasmodics 120. The most commonly prescribed antibiotic was cefuroxime 56(36.36%) followed by cefixime, azithromycin, fluconazole, ciprofloxacin, nitazoxanide, roxithromycin, metronidazole, clindamycin and flucloxacillin were 28(18.18%), 21(13.63%), 12(7.79%), 11(7.14%), 9(5.84%), 8(5.19 %), 6(3.89 %), 5(3.24%), 4(2.59%) respectively. Conclusion: In conclusion antibiotics are frequently using in the OPD of Obstetrics and Gynaecology department among the women. Bangladesh Journal of Medical Microbiology, July 2023;17 (2):77-81